Fungal Diversity and Community Assembly of Ectomycorrhizal Fungi Associated With Five Pine Species in Inner Mongolia, China - Wang, Yong-Long; Zhang, Xuan; Xu, Ying; Babalola, Busayo Joshua; Xiang, Si-Min; Zhao, Yan-Ling; Fan, Yong-Jun (Frontiers in Microbiology, 2021)
Ectomycorrhizal (EM) fungi play vital roles in ensuring host plants' health, plant diversity and the functionality of ecosystem. However, EM fungal diversity, community composition and underlying assembly processes in Inner Mongolia, China, where forests were typical semi-arid and cold-temperate zones attract less attention. In this study, we investigated EM fungal communities from 63 root samples of five common pine plants in Inner Mongolia across 1,900 km using Illumina Miseq sequencing of the fungal internal transcribed spacer 2 (ITS2) region. We evaluated the impact of host plant phylogeny, soil, climatic and spatial variables on EM fungal diversity and community turnover. Deterministic versus stochastic processes for EM fungal community assembly were quantified using -nearest taxon index (NTI) scores. In total, we identified 288 EM fungal operational taxonomic units (OTUs) belonging to 31 lineages, of which the most abundant lineages were tomentella-thelephora, wilcoxina, tricholoma and suillus-rhizopogon. Variations in EM fungal OTU richness and community composition were significantly predicted by host phylogeny, soil (total nitrogen, phosphorus, nitrogen: phosphorus ration and magnesium), climate and spatial distance, with the host plant being the most important factor. NTI demonstrated that both deterministic and stochastic processes jointly determined the community assembly of EM fungi, with the predominance of stochastic processes. At the Saihanwula (SHWL) site selected for preference analysis, all plant species (100%) presented significant preferences for EM fungi, 54% of abundant EM fungal OTUs showed significant preferences for host plants and 26% of pairs of plant species and abundant fungal OTUs exhibited remarkably strong preferences. Overall, we inferred that the high diversity and distinctive community composition of EM fungi associated with natural pine species in Inner Mongolia and the stochastic processes prevailed in determining the community assembly of EM fungi. Our study shed light on the diversity and community assembly of EM fungi associated with common pine species in semi-arid and cold temperate forests in Inner Mongolia, China for the first time and provided a better understanding of the ecological processes underlying the community assembly of mutualistic fungi.